2014
DOI: 10.1007/s11103-013-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

The role for CYCLIN A1;2/TARDY ASYNCHRONOUS MEIOSIS in differentiated cells in Arabidopsis

Abstract: The Arabidopsis A1-type cyclin, CYCA1;2, also named TARDY ASYNCHRONOUS MEIOSIS (TAM), is known for its positive role in meiotic cell cycle progression, but its function in other cells has not been characterized. This paper reports the role of CYCA1;2/TAM in differentiated cells in vegetative organs. The pattern of CYCA1;2/TAM expression was investigated by promoter and protein fusions using the β-glucuronidase and the green fluorescent protein, respectively. The relevance of the promoter region used in these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Homologous recombination was essential for accurate repair of DNA double stranded breaks (DSBs) created by highly conserved SPO11 proteins during meiosis in most eukaryotes (Shingu et al, 2012), and known genes DMC1, RAD54 , and RPA , as key mediators to regulate this process were significantly down-regulated in this pathway. The Cyclin-A1-2/TAM , known to regulate the progression of cell cycle during meiosis was the only cyclin-related gene within DNA replication pathway that was up-regulated (Jha et al, 2014). Besides, a portion of genes enriched were characterized as critical players in regulating transcription, DNA replication, DNA repair, and chromosome stability (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…Homologous recombination was essential for accurate repair of DNA double stranded breaks (DSBs) created by highly conserved SPO11 proteins during meiosis in most eukaryotes (Shingu et al, 2012), and known genes DMC1, RAD54 , and RPA , as key mediators to regulate this process were significantly down-regulated in this pathway. The Cyclin-A1-2/TAM , known to regulate the progression of cell cycle during meiosis was the only cyclin-related gene within DNA replication pathway that was up-regulated (Jha et al, 2014). Besides, a portion of genes enriched were characterized as critical players in regulating transcription, DNA replication, DNA repair, and chromosome stability (Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…TAM, BAM1, and BAM2 expression is altered in abcb1 abcb19 young flower buds It has been shown that the TAM cyclin synchronizes cell divisions during male meiosis (Jha et al 2014). To assess whether the asynchronous progression of meiosis observed in abcb1 and abcb1 abcb19 anthers is due to the altered expression of TAM, we analyzed the abundance of its transcript in abcb1 abcb19 young flower buds.…”
Section: Resultsmentioning
confidence: 99%
“…The above findings collectively show that cyclin As are a major class of cyclins that likely play indispensable roles in meiosis. In the current report, we show that the overexpression of the Arabidopsis A-type cyclin TAM by the ASK1 promoter [19] had a dominant effect that led to the production of the same male meiotic products as in the tam loss-of-function mutants. However, upon examination of the chromosome morphology and the subcellular localization of the ASY1 protein in male meiocytes from zygotene to diplotene, different effects of the overexpression and the loss of function of TAM were revealed.…”
Section: Introductionmentioning
confidence: 54%
“…It was previously reported that overexpression of TAM by the ASK1 promoter led to the production of polyploid plants [19] . To investigate the cellular basis for such an effect, a total of 36 T 1 plants were obtained from six independent transformation experiments that introduced the ASK1:TAM transgene into the wild-type plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation